A pilot study to identify the characteristic of trainee affecting the effectiveness of ship handling training on ship simulator among Malaysian seafarers - 458916 Mohd. Zambri Mohd. Zakaria; Mohd. Zamani Ahmad, supervisor; Fakulti Kejuruteraan Mekanikal (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2008